The ups and downs of mentoring relationship formation: What to expect. (November 2020) - Spiekermann, Lara; Lyons, Michael; Lawrence, Edith
Highlights: Initial attempt to model mentor relationship satisfaction over time. Frequency of measurement provides a high level of resolution. Mentor satisfaction was generally high and grew slightly over the course of the relationship. Mentor satisfaction over time was not related to mentee peer self-esteem. Abstract: The current study examines the development of formal youth mentoring relationships over time in a sample of female mentors. While benefits of youth mentoring have been shown across a variety of domains, research suggests that qualities of the mentoring relationship, including duration and satisfaction, are instrumental in determining mentee outcomes. Despite the central role of the relationship in mentoring, there is a paucity of research examining how mentoring relationships develop over time. Mentors were participants in a school-based mentoring program that is curriculum driven and includes both a group and a one-on-one component. Weekly reports of relationship satisfaction were collected from mentors. Multilevel modelling was used to analyze relationship quality over time. Relationship development was best modeled by a random-effects, random-slopes model. Satisfaction generally started high and grew slightly over the academic year. The intercept, slope and their interaction was not associated with mentee outcomes (e.g., mentee relationship satisfaction or peer self-esteem). This study is a first step towards understanding the developmental pattern of mentoring relationships as measured by mentor reports of relationship strength. Results from this study provide important information to aid in mentor training and to advance the mentoring field. Limitations of the research design include inability to make causal claims, small sample size, and lack of generalizability.